1991
DOI: 10.1016/0014-5793(91)81447-g
|View full text |Cite
|
Sign up to set email alerts
|

The rate of ATP‐synthesis as a function of ΔpH and Δψ catalyzed by the active, reduced H+‐ATPase from chloroplasts

Abstract: The H+-ATPase from chloroplasts was brought into the active, reduced state. Then, an electrochemica| potential difference of protons across the thylakoid membranes was F_,cnerated b~ ,in acid-base transition, ~lpH, combined with a K*/valinomycin diffusion potential. ~. The initial rate of ATP synthesis was measured with a rapid-mixing quenched-flow apparatus in the time-range between 20-150 ms. The rate of ATP symhesis depends in a sigmoidal way on ,dpH. Increasing diffusion potentials shifts the ApH-dcpendcnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 14 publications
(9 reference statements)
2
33
1
Order By: Relevance
“…s -I . CF,F,-' with a higher energy supply by cyclic electron transport applying phenazinemethosulfate as electron acceptor (cyclic photophosphorylation; Engelbrecht et al, 1989) or by acidbase transition combined with a K'halinomycin diffusion potential (Junesch and Graber, 1991;compare Table 1). The rates are calculated on the bases that, in thylakoids, 0.37 mg CF, are presenvmg chlorophyll (Frasch et al.…”
Section: Discussionmentioning
confidence: 99%
“…s -I . CF,F,-' with a higher energy supply by cyclic electron transport applying phenazinemethosulfate as electron acceptor (cyclic photophosphorylation; Engelbrecht et al, 1989) or by acidbase transition combined with a K'halinomycin diffusion potential (Junesch and Graber, 1991;compare Table 1). The rates are calculated on the bases that, in thylakoids, 0.37 mg CF, are presenvmg chlorophyll (Frasch et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis suggests that variant experimental conditions likely underlie conflicting evidence regarding kinetic equivalence of pmf components Δ pH and Δψ. Some in vitro studies have found that the effect of the two components of pmf are equivalent (39)(40)(41)(42), whereas others have concluded that they are not (43)(44)(45). There is no inherent reason to expect kinetic equivalence (53) because Δ pH and Δψ affect kinetics through different mechanisms: Δ pH through H + concentration, and Δψ most likely through binding affinity dictated by the thermodynamic cycle constraint, as described in SI Appendix.…”
Section: Kinetic Equivalence Of Pmf Components May Depend On Experimementioning
confidence: 99%
“…Additional analysis sheds light on contradictory reports on the "kinetic equivalence" of different components of the driving protonmotive force (pmf) (39)(40)(41)(42)(43)(44)(45)(46): should the synthesis rate be sensitive to whether the pmf is generated by a pH difference or transmembrane potential difference? We show that kinetic behavior is approximately equivalent under most physiological conditions, but that variant conditions can clearly exhibit nonequivalence.…”
mentioning
confidence: 99%
“…The chloroplast CF 0 -CF 1 -ATP synthase (ATP synthase) 2 drives the reversible synthesis of ATP from ADP and P i using energy from the light-driven proton electrochemical gradient, or proton motive force (pmf) (1,2). This multisubunit complex is composed of two subcomplexes.…”
mentioning
confidence: 99%